Effect of Compression over Electrical Admittance of Chicken Breast and Rat Breast - Moqadam, Sepideh M.; Grewal, Parvind; Golnaraghi, Farid (CMBES Proceedings, 2014)
Bio-impedance of tissue varies with the amount of applied compression. This paper presents the observed changes in vitro in bioimpedance of chicken and rat breast under various levels of compression. Soft tissue admittance at various pressure levels, is measured using bi-polar bioimpedance measurement set up and finger wearable force sensors over Ag/AgCl electrodes. Thus by changing the frequency of driving signal, multi frequency measurements at various pressure levels are obtained. Fitting the Cole-Cole model [1] to the multi-frequency admittance measurements at various pressure levels provides the mapping of parameters showing the relationship between the applied pressure and the admittance of soft tissue. The effect of pressure on bio-impedance parameters in the Cole-Cole model is deduced by means of the least square method and Cole-Cole circuit theory. Studying the bio-impedance of twenty chicken breasts and two rat breasts under compression illustrates the changes in bio-impedance of tissue resulting from the loss of fluid in the tissue.